Impacto da proteinúria sobre o aparelho endocítico tubular em pacientes com pré-eclâmpsia - Albejante, Maria Clara (2016)
The relationship between pre-eclampsia (PE) and vitamin D deficiency, two important public health problems, is increasingly under discussion. It is not known which of these clinical conditions arises first. There is evidence that one intensifies the other, especially because proteinuria, a consistent finding and factor to classify PE, can be ameliorated by vitamin D replacement. At the same time, it is possible that vitamin D activation is impaired in proteinuria, once the vitamin D-activating tubules would be losing their endocytic ability. The present study aimed to verify the relationship between vitamin D deficiency, proteinuria and loss of the tubular endocytic apparatus, in pregnant women with PE. In a first phase, 159 patient charts were surveyed between 2012 and 2013 by the obstetrics service of a public tertiary hospital in the northern region of the city of São Paulo, in order to characterize the population to be studied, as well as to evaluate the incidence of PE in two seasons, summer and winter. In a second phase, 38 patients attended by the same medical service and included in a case-control study were selected. Of these 38 patients, 12 normotensive patients constituted the Control group, 16 constituted the PE group (pre-eclamptic without proteinuria) and 10 constituted the PEP group (pre-eclamptic with proteinuria). Blood, plasma, and urine were collected for the following analyzes: proteinuria, albuminuria, 25-hydroxyvitamin D (25-VitD) and cubilin (tubular endocytic tracer marker). In addition, the expression of 10 components of the tubular endocytic apparatus was analyzed in the blood of control patients and PEP (transcriptome) patients. Of the more relevant results, we observed that the 25-VitD deficiency was highly incident in the analyzed population and was not different between the groups. The PEP group presented greater loss of cubilin in the urine and of the ten components of the tubular endocytic apparatus analyzed, six presented significantly decreased expression. The present study demonstrates the 25-VitD deficiency in a population of pregnant women in the northern part of the city of São Paulo and demonstrates that preeclamptic patients with proteinuria excrete more cubilin and lose the expression of components of the tubular endocytic apparatus, pointing to a Possible mechanism by which vitamin D deficiency can be aggravated in PE.